How different experimental models of secondary hyperalgesia change the nociceptive flexion reflex - Leone, Caterina; Di Lionardo, A.; Di Pietro, G.; Di Stefano, G.; Falco, P.; Blockeel, A. J.; Caspani, Ombretta; Garcia-Larrea, L.; Mouraux, A.; Phillips, K. G.; Treede, Rolf-Detlef; Truini, A. (Clinical neurophysiology, 2021)
Objective - In this neurophysiological study in healthy humans, we assessed how central sensitization induced by either high-frequency stimulation (HFS) or topical capsaicin application modulates features of the RIII reflex response. The ability of these stimuli to engage the endogenous pain modulatory system was also tested. - Methods - In 26 healthy participants we elicited an RIII reflex using suprathreshold stimulation of the sural nerve. Subsequently HFS or capsaicin were applied to the foot and the RIII reflex repeated after 15 minutes. Contact heating of the volar forearm served as the heterotopic test stimulus to probe activation of the endogenous pain modulatory system. - Results - HFS significantly reduced the pain threshold by 29% and the RIII reflex threshold by 20%. Capsaicin significantly reduced the pain threshold by 17% and the RIII reflex threshold by 18%. Both HFS and capsaicin left RIII reflex size unaffected. Numerical Rating Scale (NRS) pain scores elicited by the heterotopic noxious heat stimulus were unaffected by capsaicin and slightly increased by HFS. - Conclusions - HFS and capsaicin similarly modulated the pain threshold and RIII reflex threshold, without a concomitant inhibitory effect of the endogenous pain modulatory system. - Significance - Our neurophysiological study supports the use of the RIII reflex in investigating central sensitization in humans.
Gesehen am 21.11.2023